2015
DOI: 10.4238/2015.march.30.6
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of proanthocyanidin against oxidative ovarian damage induced by 3-nitropropionic acid in mice

Abstract: ABSTRACT.Oxidative stress, which poses a threat to reproductive health, causes many serious female reproductive diseases. In this study, we investigated whether proanthocyanidins (PC) have a protective effect against oxidative stress-induced ovarian damage. Forty female ICR mice were randomized into 4 groups: a control group, a control plus PC group, a 3-nitropropionic acid (3-NPA) group, and a 3-NPA plus PC group. An ovarian oxidative stress model induced by 3-NPA was constructed using female ICR mice. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
1
8
0
1
Order By: Relevance
“…Furthermore, significant increase in the fluorescence intensity of granulosa cells treated with 3-NPA also indicated that 3-NPA increased ROS products. This result is consistent with a previous study in which Zhang et al [ 26 ] reported that 3-NPA increased ROS generation in mouse ovaries. These findings imply that 3-NPA promotes ROS generation and induces oxidative stress in tissues and cells in both mammals and birds.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, significant increase in the fluorescence intensity of granulosa cells treated with 3-NPA also indicated that 3-NPA increased ROS products. This result is consistent with a previous study in which Zhang et al [ 26 ] reported that 3-NPA increased ROS generation in mouse ovaries. These findings imply that 3-NPA promotes ROS generation and induces oxidative stress in tissues and cells in both mammals and birds.…”
Section: Discussionsupporting
confidence: 94%
“…The tumor suppressor p53 plays important roles in regulating intracellular redox [ 28 , 29 ]. 3-NPA can increase the mouse ovarian ROS levels and up-regulate the apoptosis-related gene Caspase 3 in mouse granulosa cells [ 26 ]. Our results showed that in goose granulosa cells, treatment with 3-NPA at 5.0 mmol/l down-regulated the mRNA expression of Pcna and p53 , while it up-regulated Caspase 3 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…These mice were given a standard granulated food and drinking water and were divided into five groups as follows: Group 1: Mice given Oil/water (1:1, v : v ) at 5 mL/kg BW; Group 2: Mice given GSPE at 100 mg/kg b.w. GSPE was at a dose of 100 mg/kg body weight because this was reported to be the most effective dose [ 39 , 40 ]; Group 3: Mice given AFB1 in oil/water (1:1, v : v ) at 100 μg/kg b.w. ; Group 4: Mice given 1 h prior to AFB1 administration a dose of GSPE of 50 mg/kg b.w., then the dose of AFB1 100 μg/kg b.w.…”
Section: Methodsmentioning
confidence: 99%
“…Activation Direct AS101 [26], everolimus (RAD001) [27], INK128 [27], melatonin [29], ghrelin [29] Indirect AMH [31] Apoptosis Direct GnRH agonists [40,41], GnRH antagonist [42], LH [46], ATM/ATR inhibitor [21], CHEK2 inhibitor [19,24], and CK1 inhibitor [18], imatinib [48] Indirect S1P [51,61], ceramide-1-phosphate [52], zingerone [53], proanthocyanidin [54], gallic acid [55], mangafodipir [56], resveratrol [57], curcumin [58], capsaicin [58], erythropoietin [62], G-CSF [63], tamoxifen [64], dexrazoxane [65][66][67] AMH, anti-Müllerian hormone; GnRH, gonadotropin-releasing hormone; LH, luteinizing hormone; ATM, ataxia-telangiectasia mutated; ATR, ataxia telangiectasia and Rad3-related; CHEK2, checkpoint kinase 2; CK1, casein kinase 1; S1P, sphingosine-1-phosphate; G-CSF, granulocytecolony stimulating factor.…”
Section: Proposed Mechanism Of Loss Of Pfs Proposed Adjuvantsmentioning
confidence: 99%
“…In addition, it adversely affects the production of ovarian hormones and mature oocytes from healthy follicles. Of relevance to the preservation of fertility, reports suggest that the antioxidants such as S1P [51], ceramide-1-phosphate [52], zingerone [53], proanthocyanidin [54], gallic acid [55], mangafodipir [56], resveratrol [57], curcumin [58], and capsaicin [58] protect the ovary from ovotoxins including chemotherapeutic agents. Thus, oxidative stress-induced damage can be prevented by antioxidants through attenuating the free radical induced ovarian damages.…”
Section: Indirect Apoptosis By Reactive Oxygen Speciesmentioning
confidence: 99%